Building in-country capacity and expertise to ensure good governance of the deep sea minerals industry within the Pacific region. (September 2018) - Bourrel, Marie; Swaddling, Alison; Atalifo, Vira; Tawake, Akuila
Abstract: Since the 1990s, international development assistance has placed increased emphasis on good governance as a means to promote sustainable development. Many aspects of the relationship between good governance and development remain poorly understood and may vary across countries, yet it is recognised that for developing countries, a critical component resides in the ability to respond to their capacity-building needs taking into consideration individual circumstances. The interest for the DSM industry in the Pacific region stemmed from the first surveys undertaken in the 1960s on mineral deposits on the seabed of the Pacific Ocean. Since the 1970s over 100 research cruises have occurred in the Pacific region contributing to the identification of some of the world's most promising DSM resources. Recent renewed interest in commercial DSM exploration, has propelled the need for PICs to be equipped with adequate regulatory frameworks for ocean research and exploration. In 2011, SPC and the EU, initiated the SPC-EU DSM Project which had the overall objective to strengthen governance of the region's DSM. Improving human and technical capacity at a national level was at the core of the Project. This paper draws on the experience of the Project and provides an overview of capacity building needs in the Pacific region regarding DSM with a focus on the needs surrounding science, environmental management and regulatory frameworks and institutional arrangements. It discusses the achievements of the SPC-EU-DSM Project at the institutional, individual and societal levels and highlights challenges affecting the use, retention and continuous upgrading of capacities. Highlights: The technology and complexity of the DSM industry requires specific capacities. Capacity challenges faced by PICs are linked to lack of resources, which influences their approach to DSM. Limited resources hinder identification of specific capacity building needs of each PIC. In a DSM context, the dedicated nature of the SPC-EU DSM Project enabled specificities to be addressed.